Serum leptin concentrations in relation to pubertal development. Issue 5 (1st November 1997) - Carlsson, Björn; Ankarberg, Carina; Rosberg, Sten; Norjavaara, Ensio; Albertsson-Wikland, Kerstin; Carlsson, Lena M S
Abstract : OBJECTIVES: The amount of adipose tissue influences pubertal development and fertility in girls. A candidate for mediating this is the hormone leptin, derived from adipocytes. This work was carried out to determine whether the leptin concentration in serum is regulated during pubertal development. SUBJECTS AND METHODS: Serum concentrations of leptin were determined by radioimmunoassay in a sample of 252 healthy children representing all pubertal stages. RESULTS: Serum leptin concentrations correlated directly with age ( r = 0.53), body mass index (BMI) ( r = 0.71), and weight for height SD score ( r = 0.44) in girls and with BMI ( r = 0.33) and weight for height SD score in boys ( r = 0.36). Leptin concentrations increased with pubertal development in girls, resulting in significantly higher concentrations at pubertal stages 4 and 5 than at the prepubertal stage, whereas there was no change in the boys. CONCLUSIONS: Serum leptin concentrations increased during pubertal development in the girls, but remained constant in the boys. Whether the increase in serum leptin concentrations in girls is of importance for, or a consequence of, pubertal development is still to be determined.